Effect of seminal plasma infusion into the vagina on the normalization of endometrial epidermal growth factor concentrations and fertility in repeat breeder dairy cows - Dagvajamts BADRAKH; Yojiro YANAGAWA; Masashi NAGANO; Seiji KATAGIRI (The Society for Reproduction and Development, 2020)
Epidermal growth factor (EGF) concentrations in the uterus show two peaks on days 2-4 and 13-14 during the estrous cycle in fertile cows. Loss of the two peaks has been linked to reduced fertility in repeat breeder cows. This study aimed to examine the effect of seminal plasma (SP) on normalizing endometrial EGF concentrations and restoring fertility in repeat breeder cows with low EGF concentrations on day 3. In study 1, we examined the effect of the deposition sites (the vagina and uterus) of SP on the endometrial EGF concentrations in repeat breeder cows. SP infusion into the vagina, but not uterus, on the first day of the estrus cycle (day 0) normalized the endometrial EGF concentrations (≥ 4.7 ng/g tissue weight) on day 3. In study 2, the effect of SP volume (0.5 and 10 ml of SP and 0.5 ml of SP diluted to 10 ml) on EGF concentrations was examined. All groups with SP infusion had increased EGF concentrations on day 3, and cows with 10 ml of SP and 0.5 ml of SP diluted to 10 ml showed the highest levels of EGF concentrations. In study 3, we examined the effect of SP infusion on fertility. SP infusion normalized two peaks of endometrial EGF concentrations in about 60% of repeat breeder cows and produced more pregnancies than the controls (44.4 vs. 19.4%). Therefore, we concluded that SP may contain an activity to normalize the EGF profile and restore fertility in repeat breeder cows with altered EGF profiles.